Model PBL Bepedoman Asesmen Dinamis Matematika Berbantuan E- Modul dalam Mengembangkan Kemampuan Berpikir Kritis - Lesmana, Indra; Kartono, Kartono; Walid, Walid (Universitas Muria Kudus, 2023)
The aims of this research was to identify learning difficulties in mathematics and evaluate the PBL model with an E-Modul assisted mathematical dynamic assessment guideline. This research is mixed methods research with a sequential exploratory model, which was carried out on class X SMA N 1 Bulakamba students with a sample of class X MIPA 1, totaling 36 students . The first research phase was qualitative research that produced an instructional hypothesis based on a dynamic mathematical assessment. The results of this hypothesis will be used as a reference in designing the PBL model and E-Module as the next instructional instruction. The second research phase was a quantitative research and results in an evaluation of the application of the PBL and E-Modul models to critical thinking skills. The tests carried out include one sample comparison test (t test) and proportion test. The results showed that the average critical thinking ability of students after learning with the PBL model guided by the dynamic assessment of mathematics assisted by E-Modules exceeded the KKM (minimum completeness criteria) 70, the proportion of students' critical thinking skills completeness exceeded 75%, and students' abilities in the scope of representation and abstract with the category of mastering. or very mastered increased by 99.44% and 66.66%, respectively.